IDENTIFIKASI POTENSI OBYEK EKOWISATA DESA BONTO MASUNGGU, KECAMATAN TELLU LIMPOE, KABUPATEN BONE - Risma Illa Maulany; Andi Utami Batari Putri; Amran Achmad (Forestry Faculty of Universitas Hasanuddin, 2018)
The village of Bonto Masunggu is one of the villages in Tellu Limpoe District, Bone Regency. This research aims to know the potential object of ecotourism, cultural and biophysical data in the form of community in the village of Bonto Tellu Limpoe, Kecamatan Masunggu, Kabupaten Bone. There are two locations namely lane Waterfall Showdown-Showdown and the Waterfall Poko ' Pinjeng. The observed variables i.e. biological potential (flora and fauna), the potential physical and cultural community in the village of Bonto Tellu Limpoe, Kecamatan Masunggu, Kabupaten Bone. The first location is the path of the waterfall a showdown-Showdown that has high 24.9 meters and width of 18.3 meters. There are different types of Bitti (Vitex coffasus) valued economic and trade and bird species endemic to Sulawesi Thrush (Geomalia heinrichi) geomalia is included in the list of the IUCN category (NT) and the Sulawesi Hornbill (Aceros cassidix) is endemic to sulawesi at once included in the list of protected IUCN categories (VU). The second location is the path of the waterfall Poko ' Pinjeng have 41 meters and a width of 43 metres. Terapat 21 species of birds including Kring-kring yellow chest (Prioniturus flavicans) is endemic to Sulawesi which includes list of IUCN categories (NT). Key words: the potential object of ecotourism, Camping ground, Waterfall, Sapi-sapiria cave